2018
DOI: 10.1111/aos.13699
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intravitreal anti‐tumour necrosis factor drugs in adults with non‐infectious uveitis – a systematic review

Abstract: Anti-tumour necrosis factor (TNF) drugs have been extensively used in non-infectious uveitis (NIU), when corticosteroids or conventional immunosuppressive drugs cannot adequately control inflammation or intolerable side-effects occur. However, systemic anti-TNF therapies are also associated with a myriad of side-effects. Therefore, intravitreal administration of anti-TNF biologics has been employed to minimize patient morbidity and systemic adverse effects, while maintaining therapeutic effectivity. We underto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 111 publications
(325 reference statements)
0
26
0
Order By: Relevance
“…Local immune suppression with corticosteroids has a well-established role in the treatment of noninfectious uveitis 13,55,56. Since therapy with systemic anti-TNFα agents is effective, the next reasonable question is whether there is benefit from local anti-TNFα therapy 57,58. A few cases of intravitreal infliximab59 and adalimumab60,61 injection in humans have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Local immune suppression with corticosteroids has a well-established role in the treatment of noninfectious uveitis 13,55,56. Since therapy with systemic anti-TNFα agents is effective, the next reasonable question is whether there is benefit from local anti-TNFα therapy 57,58. A few cases of intravitreal infliximab59 and adalimumab60,61 injection in humans have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal administration of anti-TNF biologics has been trialled to reduce systemic adverse events. However, a systematic review concluded there is insufficient evidence to support their use due to limited efficacy with only short-term improvement 23. Lastly, a phase III study has demonstrated the efficacy of intravitreal sirolimus for NIU of the posterior segment and is a potential future local treatment strategy 24–26…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injections of 1, 1.5, and 2 mg of ADA in 4 mL of vitreous humour (0.2, 0.375, and 0.5 mg/mL) have been reported to be safe for humans. 32,33 Besides, we applied the formula for dose conversion between humans and mice (HED = NOAEL * Km ratio (for mice)) to select the highest concentration of ADA (4.61 mg/mL = 0.375 mg/ mL × 12.3). 34 To select the best effective dose the eyes of rd10 mice received a single intravitreal (ivt) dose of the following ADA concentrations: 0.125, 0.25, 0.375, 4.61 mg/ mL at P12.…”
Section: Animals and Treatmentmentioning
confidence: 99%